The impact of the COVID-19 pandemic on the country's national economy: The Indonesian experience - Algifari Algifari; Haryono Subiyakto; Isnanda Zainur Rohman (Journal of Governance and Accountability Studies, 2024)
Purpose: This study aims to examine the effects of inflation, exchange rates, and the Covid-19 pandemic on Indonesia's trade balance position and to develop an empirical estimation model to predict its position. Method: The data used in this research are the inflation rate, exchange rate of rupiah to the US dollar, export value, and import value of Indonesia from January 2012 to March 2021. The econometric model used in this study was a binary logistic regression model. Results: The results indicate that The regression coefficient of the inflation rate is negative at 0.3621, with an odds ratio of 0.696. This suggests that 1 percent in inflation reduces the probability of a trade balance surplus of 0.696. The regression coefficient for the exchange rate was positive at 2.18, with an odds ratio of 8.85. This means that every 2.72 rupiah increase in the exchange rate raises the probability of a trade balance surplus of 8.85 times. However, this study does not find empirical evidence that inflation, exchange rates, and pandemic of Covid-19 have no impact on the position of Indonesia's trade balance. Limitations: This study focuses on two factors believed to influence the position of trade balance in Indonesia: the inflation rate and foreign exchange rates. Contributions: This study provides insights into government policy.